A case of solitary pulmonary lymphangioma. Issue 5 (1st May 2003) - Nagayasu, T; Hayashi, T; Ashizawa, K; Muraoka, M; Tagawa, T; Akamine, S; Oka, T
Abstract : Solitary pulmonary lymphangiomas are rare benign lesions thought to result from the development of abnormally proliferating lymphatic vessels. This report describes a case of solitary pulmonary lymphangioma resected under video assisted thoracoscopic surgery and diagnosed using histological and immunohistochemical investigations.